EFEKTIVITAS KEBIJAKAN ALOKASI LAHAN 12,7 JUTA HA UNTUK PERHUTANAN SOSIAL - Fitri Nurfatriani; Iis Alviya (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2019)
The policy of 12.7 million ha land allocation for Social Forestry has been released since 2014. Social forestry policy places communities as the main actors in forest management. This policy is expected to be a solution to the problems of forest degradation, poverty, and land tenure conflicts. This paper aims to: (1) determine criteria and indicators priority in land allocation policy for social forestry, and (2) analyze the effectiveness of land allocation policy for social forestry. This study uses Pairwise Comparison-AHP and scoring approaches. The results show that the environmental aspect is the top priority in land allocation policy for social forestry, followed by economic and institutional aspects. From environmental aspect, the main priority is to overcome estate forest encroachment issues, while from economic, the priorty of this policy is as a source of income for the communities who live in/ around the forest. The priority of institutional aspects is finding the way of how social forestry can create market network for social forestry commercial products. In terms of social aspects, social forestry is prioritized to overcome tenure conflicts between communities and government. Based on effectiveness index, social forestry land allocation policy is categorized quite effective with the value of 10.79.